Examining EFL teachers’ changing conceptions of research: A case study of a continuing professional development program in mainland China - Kang, Yan; Yang, Luxin (Frontiers in Psychology, 2022)
Drawing on teacher interviews, written teacher reflections, teacher research proposals, and research papers, this study explored the outcome and the process of teacher learning during their participation in a continuing professional development program. It has been found that the teachers changed their conceptions of research over the course of learning concerning the nature, the purpose, and the process of research and the relationship between teaching and research. Dialogic exchanges and reading research papers, along with the scaffolding of the teacher educator, enabled the teachers to validate their practices, link others’ perspectives up to their own, and re-situate research in light of their current practices. The findings provide insights into the nature of teachers’ conceptual change, as well as how the learning opportunities can be better built into continuing professional development programs.